Clopidogrel plus indobufen in acute coronary syndrome patients with hypersensitivity to aspirin undergoing percutaneous coronary intervention. (May 2013) - Barillà, Francesco; Pulcinelli, Fabio Maria; Mangieri, Enrico; Torromeo, Concetta; Tanzilli, Gaetano; Dominici, Tania; Pellicano, Mariano; Paravati, Vincenzo; Acconcia, Maria Cristina; Gaudio, Carlo
<x xml:space="preserve">Abstract</x> The prescription of aspirin (acetylsalicylic acid (ASA)) to patients with a history of hypersensitivity to this drug could prove harmful. The aim of the study was to assess the antiplatelet activity and safety of a combined antiplatelet treatment with indobufen and clopidogrel in acute coronary syndrome (ACS) patients with hypersensitivity to aspirin, undergoing coronary stenting. Forty-two consecutive ACS patients treated with stent implantation were randomly assigned to receive clopidogrel 75 mg daily (loading dose 300 mg) plus indobufen 100 mg twice a day (group A), or clopidogrel 75 mg daily, after 300 mg of loading dose (group B). Platelet activity and safety were monitored in both groups at 1, 3, 6, 12, and 18 months with laboratory and clinical evaluation. A lower value of max % platelet aggregation to arachidonic acid and collagen was found in group A compared to group B (31.79 ± 27.33 vs. 73.67 ± 19.92; p < 0.0001 and 28.53 ± 21.32 vs. 73.58 ± 17.71; p < 0.0001, respectively). There was no difference in max % of platelet inhibition to adenosine diphosphate between the two groups (14.23 ± 18.92 vs. 10.30 ± 18.97; p = 0.23). In the population that was under indobufen treatment, the serum thromboxane B2 (TXB2) production at 1 week and 1 month was very low (2.6 ± 1.6 ng/ml and 3.0 ± 2.7 ng/ml, respectively; p = 0.82). The combined treatment was well tolerated in group A patients. This study suggests that the combined antiplatelet treatment with clopidogrel and indobufen could be a good option in ACS patients with hypersensitivity to aspirin undergoing coronary stenting.